Evaluation of Types of Insolvency Systems in Russia, Germany, and France - SANTALOVA, Marianna; FURTICHEV, Ivan; BALAHANOVA, Dariko; IVANOVA, Svetlana (Journal of Advanced Research in Law and Economics; Vol 8 No 1 (2017): JARLE Volume VIII Issue 1 (23) Spring 2017, 2017)
In the article insolvency systems of Russia, France and Germany are evaluated. Pro-debtor system is aimed at rehabilitation of the enterprise, which suffers insolvency rather than liquidation and redistribution of assets in order to repay debts in short-term period. Under this system, enterprise may use a variety of procedures, which may help escape receivership procedure (France). Pro-creditor system implies that the debtor is in charge of financial problems of the enterprise, and the main aim of this system is not the rehabilitation of the debtor, but as fast fulfillment of creditors’ claims as possible (Germany). Russian insolvency system seems to be neutral, as it provides both tools for saving business and to repay debts, and does not give any special preferences to any party